Identificação de indicadores para avaliação de mobilidade urbana inteligente: um estudo de caso em Aparecida de Goiânia - Medeiros, Bruno Pereira de (2022)
The concentration of inhabitants in large urban centers imposes several challenges on the planning and management of cities, whether related to environmental management or the adequacy and expansion of existing infrastructure. That said, smart cities (SC) initiatives have been presented as alternatives in the attempt to solve some of these problems. In this scenario, the aspect of smart urban mobility appears as one of the main axes of SCs, as it addresses the transport systems of cities and is directed related to the quality of life of the population. In this context, this study aimed to identify indicators that allow the evaluation of smart urban mobility actions and their impacts in the context of smart cities in Brazilian municipalities. This research was carried out through a hypothetical-deductive and a predominantly qualitative approach, alongside with an interpretive analysis of data in a case study in Aparecida de Goiânia. The data investigation was carried out through indirect observation techniques - systematic literature review and documentary research. As part of the results, it is pointed out that 15 finalistic MUI indicators were filtered. After contextualizing them to the reality of Aparecida de Goiânia, object of the case study, there were positive results such as the increase in the application of public spending and the reduction of deaths caused by traffic accidents. However, there is still room for the implementation of other public policies that encourage, for example, cycling and the adoption of low-emission vehicles.